Development of Media Based Learning Google Sites to Improve PAI Learning Outcomes at SMPN 15 Malang - Sa’adah, Umi Zahrotus; Husna, Zulfa Nailatul; Lathifa, Imroatul; Thoyyibah, Nadhiya Noor; Sutiah, Sutiah (Edumaspul: Jurnal Pendidikan, 2023)
Google sites is a website media that can be used in the learning process, group or personal. The aim of this research is to find out: 1) Developing a Google Sites-based learning media design for PAI learning, 2) How appropriate a Google Sites-based learning media design is for PAI learning. 3) What is the appeal of Google Sites-based learning media design for PAI learning? The research approach used in this research is Research and Development (RnD). The result of this research is the development of Google Site-based learning based on the ADDIE model and is declared "WORTH IT". So far, Google Site-based online learning media can be received by students easily, practically and effectively anytime and anywhere. Recommendations for schools or teachers are to make good use of Google Sites-based learning media so that students can follow technological developments used for learning activities. Both learning in junior high schools and learning at the next level, future researchers who will develop Google Sites-based learning are advised to follow technological developments according to what the school has, such as developing Google Site-based PAI learning so that.